Efektivitas Model Discovery Learning pada Mata Pelajaran Dasar Listrik dan Elektronika - Harisa Rahmadani; Usmeldi Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study aims to analyze the effectiveness of the discovery learning model in the subjects of Electricity Basic and Electronics class X TITL at SMK Dhuafa Padang. The design used in this research is experimental research, while the type of experimental design used is Pre-Experiment. The design used in this research is one one-group pretest and posttest design. The method used in measuring the assessment of student's skills is a skill scale assessment and is carried out through observation. Based on the results of data analysis and discussion, it can be concluded that the discovery learning model is effective for improving student learning outcomes in the subject of Electricity Basic and Electronics class X of Electrical Power Installation Engineering at SMK Dhuafa Padang. This is known from the increasing completeness of student learning outcomes. The average post-test score is higher than the pre-test score. Then the discovery learning method is also declared effective because the results of the effect size analysis are included in the large category and the competence of students' skills has reached the minimum classical value, which is at 86.68% with the predicate A (very good) and B (good).